2013
DOI: 10.3748/wjg.v19.i6.874
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal ultrasound substantiates diagnostics of bile duct strictures of uncertain etiology

Abstract: IDUS shows good results for accurate diagnostics of bile duct strictures of uncertain etiology thus allowing for adequate further clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 25 publications
0
52
0
2
Order By: Relevance
“…To further improve the diagnostic yield, advanced endoscopic imaging modalities such as intraductal ultrasound and optical coherence tomography have been applied. A large cohort study of 397 patients showed that intraductal ultrasound had a sensitivity of 93.2%, a specificity of 89.5% and an accuracy of 91.4% for discriminating benign from malignant biliary strictures . However, its diagnostic yield could be affected by prior biliary stenting or other interventions.…”
Section: Resultsmentioning
confidence: 99%
“…To further improve the diagnostic yield, advanced endoscopic imaging modalities such as intraductal ultrasound and optical coherence tomography have been applied. A large cohort study of 397 patients showed that intraductal ultrasound had a sensitivity of 93.2%, a specificity of 89.5% and an accuracy of 91.4% for discriminating benign from malignant biliary strictures . However, its diagnostic yield could be affected by prior biliary stenting or other interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, maneuverability and visualization of POCS are often limited in the very DBS because of the unstable scope position. In a retrospective analysis of 397 cases with indeterminate biliary stricture, IDUS was useful in predicting malignancy with a sensitivity, specificity, and accuracy of 93%, 89%, and 91%, respectively . However, most studies on the utility of IDUS and POCS included both hilar and DBS and did not evaluate their specific use in DBS.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic work‐up of patients presenting with bile duct obstruction remains challenging. There are various malignant diseases that can cause bile duct obstruction including cholangiocarcinoma, adenocarcinoma of the papilla of Vater, pancreatic carcinoma or metastases with consecutive compression of the common bile duct . The clinical characteristic features for malignant bile duct obstruction are variable and often not entirely clear.…”
Section: Introductionmentioning
confidence: 99%